The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1039/d1ta06237a
|View full text |Cite
|
Sign up to set email alerts
|

Pt current collectors artificially boosting praseodymium doped ceria oxygen surface exchange coefficients

Abstract: The chemical oxygen surface exchange coefficient (kchem) values used to quantify and rank oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) catalyst performance for high-temperature, oxygen-exchange-enabled devices (such as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 141 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…The change of P O during the high-temperature growth and cooling process does not cause any significant variation in the lattice constant, from which we can infer that the pressure in the given range does not impact on the V O concentration in the grown films, and that the deviation from V O concentration is small. It is well-documented that oxygen-deficient ceria and ceria-based materials have a propensity to readily react and store oxygen [23,24]. Consequently, the ability to manipulate the content of oxygen vacancies in the doped films is restricted under the prevailing high-temperature film growth conditions that encourage oxidation activities.…”
Section: Resultsmentioning
confidence: 99%
“…The change of P O during the high-temperature growth and cooling process does not cause any significant variation in the lattice constant, from which we can infer that the pressure in the given range does not impact on the V O concentration in the grown films, and that the deviation from V O concentration is small. It is well-documented that oxygen-deficient ceria and ceria-based materials have a propensity to readily react and store oxygen [23,24]. Consequently, the ability to manipulate the content of oxygen vacancies in the doped films is restricted under the prevailing high-temperature film growth conditions that encourage oxidation activities.…”
Section: Resultsmentioning
confidence: 99%
“…While the impact of surface Si on the oxygen exchange kinetics of perovskite STF35 specifically is unknown, in another composition, fluorite (Ce,Pr)­O 2−δ , severe degradation of k chem values has been attributed to Si poisoning, which could be alleviated by subsequent coating with La-oxide leading to recovery of the original, native k chem values . More recent work has suggested that Pt coatings may also interact beneficially with Si poisoning on films of that same composition …”
Section: Discussionmentioning
confidence: 99%
“…67 More recent work has suggested that Pt coatings may also interact beneficially with Si poisoning on films of that same composition. 19 Analysis of the temperature dependence of the oxygen surface exchange coefficient from experimental data and COMSOL simulations reveals further differences between the two samples. For Au-STF35, the approximate activation energy of k chem exhibits a spatial dependence: it is notably higher at the MIEC-film interface vs on the native film surface (∼1.5∼0.5 eV).…”
Section: Spectroscopic Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, Pt is well known as a catalyst for oxygen reactions [50,51] and the employed Pt buffer layer could-upon diffusion to the surface-lead to modifications of the observed oxygen kinetics of ceria. [52,53] However, no such effect was found during exchange and back-exchange experiments by comparing CGO thin films simultaneously deposited on Pt/Si and MgO single-crystal substrates, as shown in Figure S9 (Supporting Information).…”
Section: Iers For Surface Limited Thin Film Scenariomentioning
confidence: 99%